2012
DOI: 10.18097/pbmc20125805514
|View full text |Cite
|
Sign up to set email alerts
|

Variability of healthy human proteome

Abstract: 1 Учреждение Российской академии наук Государственный научный центр РФ -Институт медико-биологических проблем РАН, Хорошевское шоссе, 76-а, 123007 Москва; тел.: (499) 195-65-20; эл. почта: npakharukova@gmail.com 2 Учреждение Российской академии медицинских наук Научно-исследовательский институт биомедицинской химии имени В.Н. Ореховича РАМН Целью данного обзора является анализ работ, посвященных характеристике степени вариабельности белков и разнообразию их посттрансляционных модификаций у здорового человека.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…57 Numerous studies have demonstrated that a proteomic profile is characterized by significant intra-and interindividual variability, and quite often natural ("normal") variability of some proteins can be comparable to changes observed in pathological processes. 58 In the present study, we sought to determine interindividual plasticity of the NHOEC proteome by 2DE analysis of proteins isolated from three separate age and sex matched healthy individuals. The 2D gel profiles for these samples are shown in Figure 7.…”
Section: Interindividual Plasticity Of Primary Hoec Proteomementioning
confidence: 99%
“…57 Numerous studies have demonstrated that a proteomic profile is characterized by significant intra-and interindividual variability, and quite often natural ("normal") variability of some proteins can be comparable to changes observed in pathological processes. 58 In the present study, we sought to determine interindividual plasticity of the NHOEC proteome by 2DE analysis of proteins isolated from three separate age and sex matched healthy individuals. The 2D gel profiles for these samples are shown in Figure 7.…”
Section: Interindividual Plasticity Of Primary Hoec Proteomementioning
confidence: 99%
“…However, there seems to be no major movement toward extremely fast omic analysis of several samples per seconds for extremely large sample sets, i.e. millions or even billions of samples, despite the realization that baseline abundances of specific proteoforms or other biomolecular species can substantially vary among (healthy) individuals, in particular in the human population (19)(20)(21), and thus for diagnostic purposes ultimately demanding frequent longitudinal sampling of all individuals in a given population. Only this type of largescale sampling and subsequent (prote)omic analysis will provide the much-needed data for advancing the understanding of population-wide proteome changes and exploiting protein/ proteome analysis for improved diagnostics and therapeutics.…”
mentioning
confidence: 99%